Financial accounting - Meigs, Walter B.; Meigs, Robert F. (New York : McGraw-Hill, 1983)
With a clear and comprehensive style, this text leads readers through their studies of Financial Accounting step-by-step, perfectly balancing theory and real-life practice.
Includes index.
kjo 17/01/2019
Loans
Keywords: Accounting